Implementasi Totem untuk Penguatan Identitas Kelurahan Keputih dan Peningkatan Estetika Ruang Publik - Rachmat Santoso; Jauari Akhmad Nur Hasim; Citra Devi Murdaningtyas; Aji Sapta Pramulen; Rizky Yuniar Hakkun; Kholid Fathoni; Ibrohim Yofid Fananda; Akhmad Alimudin; Aliv Faizal M; Dwi Susanto; Hestiasari Rante; Irma Wulandari; Muhammad Agus Zainuddin; Moh. Hasbi Assidiqi; Novita Astin; Sritrusta Sukaridhoto; Widi Sarinastiti; Ahmad Huzaini; Pipid Muntoro; Aryo Quais Adisuryo Waseso; Halimatussa’Diyah; Muhammad Rakha Maulana (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
A totem is one of the visual identity elements that can strengthen the character of a public space while supporting the delivery of information to the community. This community service program aimed to design and implement a totem as a local landmark and public information medium at Simpang Lima Keputih, Surabaya, which is part of the community development area of Politeknik Elektronika Negeri Surabaya (PENS). The program was conducted through several stages, including preparation, field survey, design development, physical implementation, and evaluation. A participatory approach was applied by involving village officials, district authorities, relevant government agencies, a professional vendor, students, and local residents throughout the planning and installation processes. The program produced one totem unit equipped with acrylic letter signage displaying the word “KEPUTIH,” a bamboo logo representing a local symbol, an integrated lighting system, and a running LED display for the dynamic delivery of public information. Observation results indicated that the totem functioned as a visual landmark and improved the visibility of Simpang Lima Keputih’s identity, particularly at night. Collaboration among PENS, local government authorities, project partners, students, and the community supported the design validation, production, installation, and evaluation processes. The completed totem also provides opportunities for further development of public information media through the integration of digital technology and visual communication design.